2015
DOI: 10.1124/mol.115.100057
|View full text |Cite
|
Sign up to set email alerts
|

G Protein–Coupled Receptor Signaling Networks from a Systems Perspective

Abstract: The signal-transduction network of a mammalian cell integrates internal and external cues to initiate adaptive responses. Among the cell-surface receptors are the G protein-coupled receptors (GPCRs), which have remarkable signal-integrating capabilities. Binding of extracellular signals stabilizes intracellular-domain conformations that selectively activate intracellular proteins. Hereby, multiple signaling routes are activated simultaneously to degrees that are signal-combination dependent. Systems-biology st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 114 publications
(164 reference statements)
0
7
0
Order By: Relevance
“…However, it is the downstream effects and integration of signalling that are important. For a given cell, the challenge of understanding the action of multiple ligands on many GPCRs linked to multiple signaling routes can now be addressed using systems biology approaches to deconvolute the spatiotemporal phenomena of intracellular signal integration [ 91 ].…”
Section: Biological Validation Of Leadsmentioning
confidence: 99%
“…However, it is the downstream effects and integration of signalling that are important. For a given cell, the challenge of understanding the action of multiple ligands on many GPCRs linked to multiple signaling routes can now be addressed using systems biology approaches to deconvolute the spatiotemporal phenomena of intracellular signal integration [ 91 ].…”
Section: Biological Validation Of Leadsmentioning
confidence: 99%
“…Zero-order ultrasensitivity presumably also operates for GTP/GDP cycles when the guanine nucleotide exchange factor (GEF) and/or the GAP are operating near saturation (Roth et al, 2015). Indeed, optical manipulations of GPCR signaling in single cells were recently used to reveal such switch-like ultrasensitivity in Gi-mediated activation of PI3K in macrophages (Karunarathne et al, 2013).…”
Section: Enhancing Signaling Responsiveness With Negative Regulatorsmentioning
confidence: 99%
“…These results support the importance of many conserved cellular signaling pathways in ehrlichial survival. For example, G-protein coupled receptor (GPCR) signaling involves a variety of ligands and stimuli and can regulate a highly interconnected network of signal transductions and cellular responses (Roth et al, 2015). We found that six TRP120-interacting proteins including ADAM17, A kinase anchor protein 2 (AKAP2), C-X-C motif chemokine ligand 12 (CXCL12), G protein subunit alpha i2 (GNAI2), G protein pathway suppressor 1 (GPS1), and phosphodiesterase 1B (PDE1B), and one TRP47-interacting protein GNB1 are involved in GPCR signaling.…”
Section: Discussionmentioning
confidence: 99%